Evaluation of a Psychopedagogical Program and Its Relationship with the Development of Socioemotional Skills and School Coexistence in Secondary Education (Journal SCIENCEVOLUTION, 2026)
In the Dominican Republic, a significant participation of secondary school students in situations of school bullying has been reported, highlighting the need for educational interventions aligned with adolescents’ socioemotional development, given that this stage is characterized by a high prevalence of emotional disorders and school coexistence challenges. In this context, the objective of this study is to describe the levels of socioemotional skill development observed in students from the second cycle of secondary education at the Otilia Peláez Morning High School, Santo Domingo, Dominican Republic, following the implementation of an eight-week psychoeducational program. An integrative mixed-methods approach was employed, with a predominance of a descriptive quantitative component, complemented by an interpretive qualitative phase. The sample consisted of 128 students and 21 members of the educational staff. The instruments applied included the Emotional Intelligence Inventory (EQ-i:YV) and the Socioemotional Skills Questionnaire (CHSE), complemented by semi-structured interviews. Results showed that 88.3% of students were classified at medium and high levels on the CHSE, while 85.1% fell into moderately high or higher categories on the EQ-i:YV. Empathy reached the highest level (90.0%), whereas self-regulation showed the lowest level (82.7%), with no significant differences by sex or academic grade. Favorable levels of socioemotional development following the psychoeducational program were reported in a vulnerable context, with particular emphasis on interpersonal skills, while also revealing the need to strengthen emotional self-regulation in future interventions.
Keywords: Socio-Emotional Skills; Emotional Intelligence; School Coexistence; Secondary Education; Psychopedagogical Program; Social-Emotional Learning; Dominican Republic